ANALISIS DESAIN PEMBELAJARAN CULTURALLY RESPONSIVE TEACHING DALAM KONTEKS PENGUATAN LITERASI HUMANISTIK DI SEKOLAH DASAR - Yaasmin, Labiibah Shafiyyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Indonesia is rich in cultural wealth. However, our education has not fully appreciated that wealth. Education in this modern era uses an independent curriculum and integrates culture. In this Merdeka curriculum, there is a learning model, namely Culturally Responsive Teaching (CRT) which is integrated with culture because this is in accordance with 21st century learning. The teaching method called Culturally Responsive Teaching (CRT) is an approach method that connects the cultural background of students with the subject matter in an explicit and directed manner. 21st century learning is also associated with literacy that is adapted to the times. Humanistic literacy is the cornerstone of social behavior and involvement in social life, it is very important to improve. So that the purpose of this study is to strengthen humanistic literacy with a Culturally Responsive Teaching (CRT) approach in the context of introducing cultural richness so that students can understand the cultural diversity that exists in Indonesia, and they become humans who can appreciate and tolerate cultural richness around their environment. This type of research uses interpretive qualitative, meaning a specific approach to research design, concept formation, data analysis and standards. The application of the Culturally Responsive Teaching (CRT) approach is very feasible in optimizing humanistic literacy in elementary schools. This learning design emphasizes the importance of understanding and enhancing students' social foundation values, as well as incorporating their social values and honing learning preparation.